2001
DOI: 10.1021/bi015678l
|View full text |Cite
|
Sign up to set email alerts
|

NMR Structure of a Gemcitabine-Substituted Model Okazaki Fragment

Abstract: Gemcitabine (2'-deoxy-2',2'-difluorodeoxycytidine; dFdC) is a potent anticancer drug that exerts cytotoxic activity, in part, through incorporation of the nucleoside triphosphate dFdCTP into DNA and perturbations to DNA-mediated processes. The structure of a model Okazaki fragment containing a single dFdC substitution, [GEM], was determined using NMR spectroscopy and restrained molecular dynamics to understand structural distortions that may be induced in replicating DNA resulting from dFdC substitution. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 29 publications
(45 reference statements)
1
44
0
Order By: Relevance
“…Similarly, dFd-CMP also decreased the binding affinity of the next 2 downstream nucleotides by 6 -10-fold before recovering to normal. The predicted decrease in the structural integrity of the DNA duplex caused by the presence of a dFdCMP moiety with a 3Ј-endo pucker is supported by the fact that the melting temperature of the 12-bp Okazaki fragment is lowered by 4.3°C in the presence of an internal dFdCMP (44). Such a noncanonical conformation of dFdCMP in a template should also affect the positioning of an incoming dNTP for in-line attack by the primer's 3Ј-OH group during phosphodiester bond formation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, dFd-CMP also decreased the binding affinity of the next 2 downstream nucleotides by 6 -10-fold before recovering to normal. The predicted decrease in the structural integrity of the DNA duplex caused by the presence of a dFdCMP moiety with a 3Ј-endo pucker is supported by the fact that the melting temperature of the 12-bp Okazaki fragment is lowered by 4.3°C in the presence of an internal dFdCMP (44). Such a noncanonical conformation of dFdCMP in a template should also affect the positioning of an incoming dNTP for in-line attack by the primer's 3Ј-OH group during phosphodiester bond formation.…”
Section: Discussionmentioning
confidence: 94%
“…Following dFdCTP incorporation, the DNA primer terminated with 3Ј-dFdCMP is likely to adopt the 3Ј-endo pucker conformation as observed in the solution structures of gemcitabine embedded in DNA (44). The electron density of its 3Ј-OH group should be lowered by the electron-withdrawing fluorine group, thereby rendering the 3Ј-OH group less nucleophilic.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the arabinose sugar moiety in AraC and the difluoro group on the 2Ј-position of the sugar moiety of dFdC alter the DNA structure, inhibiting DNA polymerases (11,12). The cytotoxicity of AraC or dFdC is proportional to the amount of the analog incorporated into DNA (6 -8).…”
mentioning
confidence: 99%
“…Several mechanisms have been reported, including enzymes involved in modulating the nucleotide pool (28), or DNA exonuclease that can remove these analogs from the 3 0 termini of DNA and therefore diminish their activities (27). Structural and mechanistic studies showed that the arabinose sugar moiety of AraC and the di-fluoro group on the 2 0 position of the sugar moiety of dFdC alter the DNA structure, which significantly reduced the extension efficiency for replicative DNA polymerases (41,54). In comparison, pol Z efficiently extends from either AraC or gemcitabine at the 3 0 termini of DNA (22).…”
Section: Dna Polymerase Eta and Anticancer Agentsmentioning
confidence: 99%